2022
DOI: 10.1007/s12032-022-01922-6
|View full text |Cite
|
Sign up to set email alerts
|

Contracting triple-negative breast cancer with immunotherapeutic armamentarium: recent advances and clinical prospects

Abstract: Triple negative breast cancer (TNBC) portraying deficient expression of estrogen receptor (ER), progesterone receptor (PR) and Human epidermal growth factor receptor 2 (HER2) is known to be the most aggressive subtype associated with poor prognosis and interventional strategies limited to chemotherapy and breast conserving surgery. Some TNBC incidences have also been reported with positive circ-HER2 expression thus rendering circ-HER2 a potential immunotherapy target to direct drug development. Resistance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Finally, therapeutic CVs have been developed to target TAAs, such as mammaglobin-A and HER2. While the efficacy of therapeutic vaccines in BC is still being studied, early-phase clinical trials have shown encouraging results, with some patients experiencing immune responses and disease stabilization [222].…”
Section: Therapeutic Cancer Vaccinesmentioning
confidence: 99%
“…Finally, therapeutic CVs have been developed to target TAAs, such as mammaglobin-A and HER2. While the efficacy of therapeutic vaccines in BC is still being studied, early-phase clinical trials have shown encouraging results, with some patients experiencing immune responses and disease stabilization [222].…”
Section: Therapeutic Cancer Vaccinesmentioning
confidence: 99%